The earthship concept - Ekvall, Martin (2019)
I will in this master thesis study a building concept called Earthship. Designed to be autonomous, built out-of earth, tires and as much reused material as possible in order to be a self-sufficient, environmental friendly building that transcends monthly payments for its inhabitants. The study aims to research the Earthship concept and its consumers from an economic and environmental perspective in relation to conventional buildings in order to enable a more environmental friendly society. It does so by using a qualitative social science research approach, based on a pragmatic and post-positive research view as well as a “flexible” research design strategy. An illustrative case study of the Earthship concept was carried out through a literature review of: 1) sustainable buildings, 2) earth-sheltered housing compared to conventional housing, 3) Earthships and 4) off-grid builder. Four in-depth interviews of Earthship builders was also conducted. Relating the findings to a multiple theoretical view on modern economics and by using Positional Analysis, the Earthship concepts was found to have many favorable qualities compared to conventional buildings, especially when it comes to using used tires as earth building blocks, energy efficiency and water usage. The results from the interviews shows that Earthship consumers are found to be interested in the environment, transcending human grids and monthly bills, they also seem to trust the founder and personification of the Earthship concept, Michael Reynolds. The findings support previous research within sustainable building and Earthships in that the return to investment and the role of the project manager are central for accomplishing socially and environmentally successful building concepts. It further finds that there is a potential monetary business case for the Earthship building concept in terms of monetary profits. But, in order to be able to make such a claim we need to see beyond conventional Neoclassical economic theory and to embrace other economic assumptions.